An examination of trust as a strategical factor of success in logistical firms - Oláh, Judit; Karmazin, György; Fekete, Mária Farkasné; Popp, József (Business: Theory and Practice, 2017)
The aim of this research is to examine the effect of the role and level of in-sector trust (involving clients, subcontractors, and other logistics providers) and trust within firms in creating competitiveness in logistics service providers. The data were collected from 51 logistics service providers in Hungary. During our research we established that trust related to staff is decisive in the direction of the firm’s profitability, and the trust communicated by the top manager (trust in partners) is essential in ensuring smooth operations and long term, stable flexible cooperation. The results of this paper effectively support logistics service providers in finding economic success factors, thanks to which they can completely satisfy the expectations of customers in the supply chain.